Demulsification of water-in-crude oil emulsions via microwave heating technology - Hoo, Seng Tatt (2010)
Traditional methods to separate water-in-crude oil emulsions like chemical demulsifiers are not environmentally-friendly, slow, separation not efficient, not cost effective and consume space for separation. The potentials of microwave energy in demulsification of water-in-crude oil emulsions were investigated. In this study, stability tests, gravity settling, microwave heating and microwave separation were studied. Microwave demulsification was applied in 50/50 and 20/80 water-in-crude oil emulsions with microwave exposure time varied from 120-180 seconds. As the sludge is heated, viscosity is lowered, and rapid coalescence of liquid phases takes place. Once the liquid phases coalesce, separation occurs through natural gravity. No chemicals are needed to force separation. Three different parameters were being investigated on the effect of separation namely volume ratio of water-in-oil emulsions, different emulsifiers and power generations of microwave. The four emulsifiers used were SDDS, Span 83, Triton X-100 and Tween 80. The power generations were 360 and 540 watts respectively. 20/80 water-in-crude oil emulsion was the most stable among two volume ratios. Newtonian fluid was determined from stability tests. Viscosity decreased, shear stress increased and shear rate increased over rpm. Surface and interfacial tensions were determined. Water and oil separation efficiencies via gravity settling were low. Volumetric heat generation rate of microwave was high. Water and oil separation efficiencies of microwave were more efficient than gravity settling. Microwave causes molecular rotation and ionic conduction thus fast heating.